Drone-based services taking off to transform Africa's agriculture - Rambaldi, Giacomo (Technical Centre for Agricultural and Rural Cooperation, 2019)
Africa's agriculture sector is being progressively transformed into a high-tech industry through digital services. Decisions are being based on real-time gathering and processing of data, feeding into increasingly effective decision support systems. Unmanned aerial systems (UAS) are an integral part of this digital revolution.